A 2.0 V capacitive device derived from shape-preserved metal nitride nanorods. (August 2016) - Zhu, Changrong; Sun, Yanfeng; Chao, Dongliang; Wang, Xinghui; Yang, Peihua; Zhang, Xiao; Huang, Hui; Zhang, Hua; Fan, Hong Jin
Abstract: A high working voltage and fast charging/discharging capability are important to a supercapacitor device in order to achieve decent energy densities with high power. In this work, we report 2.0 V quasi-solid-state symmetric capacitive device based on Fe2 N-Ti2 N (FTN) core-shell nanorod array electrodes. Through a surface protection by a thin and ultra-stable Ti2 N shell, Fe2 N converted from its oxyhydroxide precursor inhibits the original nanorod structure. Due to advantageous features of these core-shell metal nitride electrodes (e.g., high conductivity, structure stability, direct current path), the symmetric device permits ultrahigh scan rates (up to 50 V s −1 ) and delivers fairly stable capacitance in long-term cycles ( 82 F g −1 with 99% capacitance retention in 20, 000 cycles). As a result, the supercapacitor exhibits an impressive energy density of 48.5 W h kg −1 at the power of 2700 W kg −1 . These results demonstrate the potentialities of metal nitride nanorods array for high energy density capacitive device. Graphical abstract: Highlights: High voltage (2.0 V) and ultrafast (scan rates up to 50 V/s) capability of symmetric supercapacitor device; capacity retention of nearly 100% upon 20, 000 cycles. Fe2 N nanorods array is realized assisted by ALD TiO2 ; previous Fe2 N are all nanoparticles. The Ti2 N thin shell is both a conductive pathway and stable protection layer to Fe2 N.